PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA MATERI SISTEM PENCERNAAN MANUSIA - Ndruru, Aperius (TUNAS : Jurnal Pendidikan Biologi, 2024)
The background to this research is the development of student worksheets based on Discovery Learning. This research aims to produce interactive learning media products on the human digestive system that are valid, practical and effective. This type of research is the development of the PLOMP model. The research method used in this research is research and development. This research was tested on 20 class VIII students at SMP Negeri 1 O'o'u. To standardize products, three test stages are carried out, namely: validity test, practicality test, effectiveness test. The instruments used are assessment questionnaires using a Likert scale and evaluation test questions to determine student learning outcomes. The research results show that the Discovery Learning-based LKPD is very valid with a presentation of 85% and is suitable for use. The average value of practicality assessed by teachers is 3.48 and students are 3.64 in the very practical category. Student motivation results are at 86% with a cognitive average of 88.7. The suggestion given by the researcher is that science-biology subject teachers should use LKPD as teaching materials in the teaching and learning process because it can increase students' interest and motivation to learn. Through this teaching material, students can broaden their horizons regarding science-biology learning on the subject of the human digestive system. For future researchers, this student worksheet can be used as reference material in research